Greenhouse gas emission forecasts for electrification of space heating in residential homes in the US. (April 2022) - Pistochini, Theresa; Dichter, Mitchal; Chakraborty, Subhrajit; Dichter, Nelson; Aboud, Aref
Abstract: This study aims to inform policymakers about the greenhouse gas emission impacts of heat pump deployment in residential homes. Electric heat pumps eliminate direct burning of fossil fuels in homes but result in indirect emissions due to fossil fuels burned for electricity production. This paper presents the first detailed emission forecasts for operating either a heat pump or gas furnace for residential heating over a 15-year period, starting in year 2022 through 2036, in six regions across the US. The study accounted for long-run marginal emissions from electricity generation, emissions from natural gas combustion in homes, and fugitive methane and refrigerant emissions from leaks. The population weighted US average results show emission reductions for a heat pump over furnace to be 38–53% for carbon dioxide, 53–67% for 20-Year global warming potential (GWP), and 44–60% for 100-Year GWP, with reductions increasing over time. The impact of fugitive emissions from the furnace is significantly higher than that of the heat pump. While more energy efficient construction reduces overall emissions for both heating types, the forecasted percent emission reduction for replacement of a gas furnace with heat pump was not impacted by changes in home construction parameters. Highlights: Residential heat pumps reduce carbon dioxide emissions by 38–53% over a gas furnace. Residential heat pumps reduce 20-Year global warming potential emissions by 53–67%. Energy efficient construction reduces overall emissions for heat pumps and furnaces. Percent emission reductions were not impacted by home construction parameters. Emission reductions were highest in the Pacific and Northeast regions.